2022
DOI: 10.3390/su14138008
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Access to the Public Debt Market on Corporate Financing Decisions: The Case of REITs

Abstract: We examined the effects of access to public debt on the corporate financing decisions in real estate investment trusts (REITs) using a difference-in-differences approach and a propensity score approach. The introduction of credit ratings by S&P and Moody’s has allowed REITs to access the public debt market. To investigate the impacts of the introduction of credit ratings, we compared the financing policies in REITs with initial credit ratings before and after the introduction of credit ratings with REITs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…In addition, examining the effects of access to public debt on corporate financing decisions in real estate investment trusts (REITs), Shen and Chau (2022) suggested that the introduction of credit ratings reduced information asymmetry and affected REITs' capital structure decisions and the level of cash holdings. It was also found that the overall risk perception level of equity investors was moderate and that the main factors affecting their risk perception aware information screening, investment education, fear psychosis, fundamental expertise, technical expertise, familiarity bias, information asymmetry, understanding of the market, etc.…”
Section: Literature Review Information Asymmetrymentioning
confidence: 99%
“…In addition, examining the effects of access to public debt on corporate financing decisions in real estate investment trusts (REITs), Shen and Chau (2022) suggested that the introduction of credit ratings reduced information asymmetry and affected REITs' capital structure decisions and the level of cash holdings. It was also found that the overall risk perception level of equity investors was moderate and that the main factors affecting their risk perception aware information screening, investment education, fear psychosis, fundamental expertise, technical expertise, familiarity bias, information asymmetry, understanding of the market, etc.…”
Section: Literature Review Information Asymmetrymentioning
confidence: 99%